Analysis of surgical outcomes and risk factors after gonioscopy-assisted transluminal trabeculotomy - Murat Gunay; Adem Turk; Omer Koksal Kurutas; Cigdem Ates; Dilek Uzlu; Busra Kose (BMC Ophthalmology)
Abstract Purpose This study aims to evaluate surgical outcomes as well as determine risk factors following gonioscopy-assisted transluminal trabeculotomy (GATT). Methods Retrospective observational study including 185 eyes (185 patients, mean age 66.7 ± 10.7 years) who underwent GATT procedure. Intraocular pressure (IOP), best-corrected visual acuity (BCVA), antiglaucoma medication (AGM) changes and surgical success rates (IOP reduction ≥ 30% from baseline and IOP < 18 mmHg, < 15 mmHg and < 12 mmHg, as Criterion A, B and C, respectively) were assessed. Cox regression analysis was used to identify risk factors in this study. Results Mean baseline and last visit IOP, BCVA and number of AGM were 32.8 ± 7.7 mmHg, 0.49 ± 0.58 and 3.8 ± 0.4, and, 12.5 ± 3.4 mmHg, 0.27 ± 0.49 and 1.7 ± 1.1, respectively. Changes in IOP, BCVA and number of AGM were significant at last visit compared to baseline (p < 0.05). Cumulative surgical success rates for Criteria A, B and C were, 86.4%, 84.7% and 54.7% at the end of the follow-up. Absence of postoperative IOP spike, age (> 60 years), mild glaucomatous damage and having pseudoexfoliation glaucoma (PEXG) were associated with higher complete surgical success for all success criteria. Qualified success rate was significantly higher in PEXG eyes than in non-PEXG eyes based on Criterion C (p < 0.0001). Complete success rates were significantly higher in PEXG eyes compared to non-PEXG eyes for all success criteria (p < 0.05). Conclusion Postoperative IOP spikes, age ≤ 60 years and moderate-severe glaucomatous damage were associated with failure for complete surgical success after GATT. PEXG was a potential factor to be associated with higher surgical success even under lower target IOP levels compared to other forms of glaucoma.